Policing political mega-events through 'hard' and 'soft' tactics: reflections on local and organisational tensions in public order policing. (2nd January 2019) - Whelan, Chad; Molnar, Adam
ABSTRACT: Public order policing has long been a central area of concern for policing political mega-events. Following the Toronto 2010 Group of 20 (G20) meeting, however, public order policing policy and practice attracted renewed attention that has had a considerable influence on subsequent political mega-events. The Toronto G20 involved up to 20, 000 protesters, over 1000 arrests, and widespread criticisms against the Toronto Police Service and Royal Canadian Mounted Police regarding excessive use of force. Using the Brisbane 2014 G20 as a case study, this article reflects on the localised tensions involved in public order policing in the context of political mega-events. We look inside the operations of Brisbane 2014, which was heavily influenced by the events from Toronto 2010, to focus on the tensions that underpin public order policing tactics in the context of political mega-events and call attention to the significance of these tensions in shaping policing policy and practice. More particularly, we examine how tensions between competing perceptions of risk amongst security actors in relation to more formal preferred strategies and tactics to manage risk can shape various public order policing outcomes. We trace these local and organisational tensions as they relate to so-called 'hard' tactics such as intelligence operations and spatial containment strategies and 'soft' tactics such as negotiated management strategies and relationship building with protest groups.